Influence of various corn syrup types on the quality and sensory properties of gelatin-based jelly confectionery - Bulca, Esra Nur; Akdeniz, Esra; Mutlu, Zeynep; Tireki, Suzan; Karimidastjerd, Atefeh; Toker, Omer Said (SPRINGER, 2024)
Jelly candies are soft confectionery products primarily composed of sucrose, corn syrup and gelling agents. This study investigates the impact of six different corn syrup, all used at constant amount (46.22%), on the physicochemical (moisture content, pH, Colour), texture and sensory properties of gelatin-based jelly samples. The Moisture content, pH, colour, and texture properties of samples were analysed at 0th, 15th, 30th, 45th, and 60th day during storage. Before storage moisture content of the candiesranged from21.03 to 22.57% whereas after 60 days, it was found between 19.31 and 20.72%. Sample JF42 exhibited the least moisture rate loss. The type of corn syrup did not significantly affect the pH of the samples. Samples with higher fructose content in the corn syrup had the lowest hardness, whereas the sample with the highest maltose content exhibited the highest hardness. Changes in gumminess and chewiness paralleled variations in hardness results. Hardness and gumminess were found suitable to follow up gelatin-based samples storage using the zero-order kinetics modelling. Corn syrups with high fructose amounts intensified the redness, while those with high glucose levels led to yellowness in the candies. In sensory evaluation, products made with G40, G60, and M50 corn syrups received higher general Understanding how various types of corn syrup impact the candies quality helps producers optimize their formulation. This information enables producers to mitigate quality deterioration during storage, ensuring that their candies maintain at the desired level and appeal to consumers.
Keywords: Confectionery; Corn syrup; Gelatin; Jelly; Sensory analysis; Shelf life; Texture; MICROSTRUCTURE; FORMULATION; MOISTURE; CANDY; GELS; Food Science & Technology